2011
DOI: 10.2134/agronj2010.0411
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Analysis of Spatial Variability in Economic Yield Response of Corn to Nitrogen Fertilization

Abstract: Despite growing interests in variable‐rate nitrogen (VRN) fertilizer applications, we still lack basic knowledge and practical methodology for identifying major factors that can be used to guide VRN application to corn (Zea mays L.). The objective was to develop a methodology for identifying a predictable relationship between economic yield response (YR) to N and commonly measured soil and terrain attributes in the presence of spatial dependence. Six 30‐ha no‐till fields in central Iowa were studied during 6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…It has been reported that rainfall amounts observed in May right before N fertilizer applications and in June just after N applications are the most interesting, because fertilizer nitrate content is subject to mobilization by water (Kyveryga et al, 2011). Another reason for interest is the fact that the few days before and right after the N application, rainfall has a positive effect on N response (Herlihy and O'keeffe, 1987;Tremblay et al, 2012).…”
Section: Economical Optimal Nitrogen Rate Asmentioning
confidence: 99%
“…It has been reported that rainfall amounts observed in May right before N fertilizer applications and in June just after N applications are the most interesting, because fertilizer nitrate content is subject to mobilization by water (Kyveryga et al, 2011). Another reason for interest is the fact that the few days before and right after the N application, rainfall has a positive effect on N response (Herlihy and O'keeffe, 1987;Tremblay et al, 2012).…”
Section: Economical Optimal Nitrogen Rate Asmentioning
confidence: 99%
“…However, climatic conditions, fertilization, soil quality, irrigation, soil management and crop rotation systems are key factors of success that vary widely among agroecosystems. Uncertainty in optimum nutrient dosage often leads growers to apply ‘insurance’ fertilization against the risk of yield loss 7 . Excessive fertilization leads not only to economic loss but also to increased incidence of diseases 8 11 , product loss during storage, and environmental damage such as nitrate leaching and N 2 O emissions 12 and surface water eutrophication by phosphates 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Large uncertainty in EORN assessment often leads growers to add "insurance extra N" against risk of yield loss [17][18][19]. A great challenge is to predict site-specific EONR accurately [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%